Presidential debates : fifty years of high-risk TV - Schroeder, Alan, 1954- (Columbia University Press, 2008)
Alan Schroeder's popular history now covers the 2000 Bush-Gore and 2004 Bush-Kerry debates, including innovations in format and press coverage, and adds new research on televised debates since 1960. Schroeder organizes his book according to a television production timeline, highlighting the importance of pre- and postdebate periods, as well as the live telecasts themselves. He describes production in painstaking detail, from the selection of questioners to camera angles, from makeup to lighting and set design. Televised debates represent a rare departure from well-choreographed c.